Organisational injustice in UK frontline services and onset of Moral Injury, Post Traumatic Embitterment Disorder (PTED) and PTSD - Carter, Claire (International journal of law, crime and justice, 2021)
Organisational injustice, betrayal, moral transgression, wrongdoing, or breach of deeply held values and beliefs can manifest in frontline staff as Post Traumatic Embitterment Disorder (PTED), Moral Injury and/or PTSD (Post Traumatic Stress Disorder). PTED and Moral Injury are fundamentally the same and could not be discriminated from each other. The constructs of PTED and Moral Injury can be assimilated into that of PTSD, rather than exist as comorbid conditions. Chronic embitterment is of clinical significance and often a symptom of PTSD, which may be inextricably linked to the traumatic incident(s) and often expressed as persistent blame of self or others, in DSM-5 diagnostic criteria for PTSD, D2 and D3. Chronic embitterment and moral pain can maintain PTSD symptoms.